The Codification of Medical Morality
VIII, 232 p.
Keywords: The editors have incurred many debts in preparing this book, and both etiquette and ethics would be contravened if they were not discharged here. Above all, we wish to thank the contributors for so cheerfully complying with our suggestions for preparing their papers for publication and efficiently meeting our schedules. It is thanks to their cooperation that this volume has appeared speedily and painlessly; their revisions have helped to give it internal coherence. This volume has emerged from papers delivered at a conference on the History of Medical Ethics, held at the Wellcome Institute for the History of Medicine, London, 1 December, 1989. We are most grateful to the Wellcome Trust for having underwritten the costs of the conference, and to Frieda Houser and Stephen Emberton whose organizational skills contributed so much to making it a smoothly-run and enjoyable day. In addition to the papers delivered at the conference, we are delighted to have secured further contributions from David Harley and Johanna Geyer-Kordesch. Our thanks to them for their eager help. From start to finish, we have received splendid encouragement from all those connected with the Philosophy and Medicine series, especially Professor Stuart Spicker, and Martin Scrivener at Kluwer Academic Publishers. Their enthusiasm has lightened our load, and expedited the editorial process.